UTILIZATION AND PROTECTION OF REGIONAL AUTONOMY-BASED ASSETS TO INCREASE LOCAL REVENUE - Sri Winarsi; Agus Sekarmadji; Oemar Mochtar (Jurnal Dinamika Hukum, 2017)
Land status of management rights of Surabaya City Government known as green letter (surat ijo) sparks controversy among citizens regarding the control and management of the land. Citizens want the controlled land will be certified, but it is constrained by the authentication of land rights in Government Law Number 24 The year 1997 on Land Registration. The method used is statute approach and conceptual approach. An analysis is conducted qualitatively by pointing out the principles and procedural law as well as analyzing social, economic and political factors in the procedural and substantive process of case completion. Factors causing the local government reluctant to release regional assets is the issue to discuss in this paper to increase local revenue derived from the utilization of local land through giving Land Use Permit and Building Rights Title (HGB) above the land of management rights. The result shows that comprehensive inventory management through the registration of management right certificate of local government for the sake of protection and legal certainty is necessary.Keywords: Management Rights, Local Finance, Local Government, Local Revenue